Antioxidant, radical scavenging and antimicrobial activities of red onion (Allium cepa L) skin and edible part extracts - Škerget, Mojca (Array, 2009)
Summary: The antioxidant, radical scavenging and antimicrobial activities of extracts from skin and edible part of red onion have been investigated. Crude extracts of red onion were obtained separately with acetone, ethanol and mixtures of solvents with water. The amounts of isolated phenolic compounds and quercetin from onion skin were approximately 3 to 5 times higher as from the onion edible part. Antioxidant and radical scavenging activities of onion skin extracts were generally high, results were comparable to that of BHT. Extracts from onion edible part showed somewhat lower activity. Furthermore, high activity of skin extracts against bacteria Escherichia coli, Pseudomonas fluorescens and Bacillus cereus and fungi Aspergillus niger, Trichoderma viride and Penicillium cyclopium was observed. Antimicrobial activity of edible part extracts against tested microorganisms is generally lower, while for Escherichia coli no growth inhibition was observed